Effect of azolla green manure on wetland rice and available of azolla-N - Abu Bakar, Rosenani (Malaysian Society of Soil Science, 1997)
A pot experiment and a field experiment were conducted to investigate the effect of Azolla pinnata, applied alone or in combination with urea, on rice plants under Malaysian conditions. Results of the pot experiment show that application of azolla significantly increased the number of tillers and panicles, dry straw weight and grain yield over the control; similar results were obtained from the application of urea. There was no significant difference between the various azolla treatments. In the field, the recovery rate with azolla application at 30 DAT was higher than when applied at transplanting; results with urea-N application were similar.